The global prevalence of sexual dysfunction in men with thyroid gland disorders: a systematic review and meta-analysis - Salari, Nader; Fattahi, Negin; Abdolmaleki, Amir; Heidarian, Pegah; Shohaimi, Shamarina; Mohammadi, Masoud (Springer, 2024)
Introduction fluctuation in serum levels of thyroid hormones or thyroid-associated dysfunction can negatively affect the sexual behaviors or performance, and disruption in couples` relationship or satisfaction. Thus, this systematic review and meta-analysis study was aimed to investigate the global prevalence of sexual dysfunction in men with thyroid gland disorders (TGD). Methods this systematic review and meta-analysis study conducted based on PRISMA statement criteria regarding the available evidences representing the prevalence of sexual dysfunction in men with TGD. The initial searching process was applied on July, 2023. In this era, the main keywords of “Prevalence”, “Sexual disorders”, “Sexual disorder”, “Sexual dysfunction”, “Male sexual dysfunction”, “Erectile dysfunction”, “Males”, “Men”, “Thyroid disorders”, “Thyroid diseases”, “Hyperthyroidism”, “Thyroid”, and “Thyroiditis” were hired. Also, “AND” and “OR” operators were used for keywords combination. All intended studies were searched using the databases of Web of Science, Google Scholar, Scopus, ScienceDirect, PubMed, and Embase. Random effects model was used to perform the analysis and the heterogeneity of the studies was assessed through I2 index. Data analysis was applied with CMA software (v.2). Results following the assessment of 17 eligible studies with a sample size of 501 individuals, the global prevalence of male sexual dysfunction with TGD was found 51.5% (95% CI:38.7–64). Also, the prevalence of male sexual dysfunction in hypothyroidism and hyperthyroidism cases was 59.1% (95% CI:37.2–77.8) and 41.5% (95% CI:25.9–59.1), respectively. The meta-regression analysis showed that following incremental trend in sample size, the global prevalence of male sexual dysfunction with TGD decreases. This assessment also revealed that the prevalence of male sexual dysfunction increases with the year of study conduction, significantly (p < 0.05). Conclusion the global prevalence of sexual dysfunction in men with TGD was found relatively high. also, the highest prevalence of sexual disorders was reported in hypothyroid cases. Thus, health policymakers are suggested to inform the individuals prone to this pathology regarding the negative effects of TGD on sexual dysfunction. Besides, TGD-affected cases can prevent sexual disorders and unpleasant consequences through timely medical treatments.